Experimental study on whole process of river blockage and dam break under different hydrodynamic conditions - Niu, Zhipan; Meng, Chuke; Xu, Weilin; Di, Baofeng; Long, Yi; Yang, Hang (Frontiers in Earth Science, 2023)
River blockage and dam break usually occur in mountainous areas with many valleys, and are frequent and extremely harmful natural disasters. With the construction of infrastructures in mountainous areas, the demand for disaster prevention and control has been further increased. Based on an innovative flume model for simulating whole process of river blockage and dam break, the present study carried out eight groups tests under different inflow rates. In the analysis, the whole process of river blockage and dam break was divided into four stages: ESBA (Early stage of blockage), LSBA (Late stage of blockage), ESBK (Early stage of breaking) and LSBK (Late stage of breaking). By analyzing the relationship between Qin and Qmax, it is found that Qmax shows an overall trend of increase with the increase of Qin while some contrarily decreasing Qmax cases exist when Qin slightly increases. The cases of irregularities may come from the inflow condition impact and randomness during the dam formation process. In addition, the slope of the curve Qin–Qmax/Qin parameter shows a decreasing trend with the increase in the median particle size of the soil. The present study proposes a new method for model experiments, providing new ideas for subsequent model experiments. Furthermore, these conclusions can provide reference for disaster prevention and mitigation in mountainous areas.